Analysis of Strategic Study of Women's Economic Empowerment Program - Yuliana, Indah (IQTISHODUNA, 2020)
Research objectives; (a) Identify the context of program empowerment undertaken, (b) Conduct an analysis of program approaches and interventions, and (c) Conduct an achievement analysis. In this study, the approach used is a case study approach as part of qualitative research. This research took place in several villages in Blitar that received the Poverty Feminization program. Sampling in this study using the snowball sampling method. Data collection techniques used in this study were interviews and observation. Data analysis is done by organizing the data, breaking it down into units, synthesizing it, arranging it into patterns, choosing what is essential and which is not essential and what will be learned, and making conclusions. The results showed (1) The context of the empowerment of this program was the head of the women's household, (2) The stages in the implementation of women's economic empowerment were carried out from the upstream to downstream sectors including the preparation phase, the assessment stage, the realization of aid, the implementation of monitoring, and the intervention of the Jalin Matra program implementation. (3) Achievement, economic empowerment carried out through poverty feminization prevention programs in general, provide positive values for the lives of the target KRTP.